Tb1, a Neurotoxin from Tityus bahiensis Scorpion Venom, Induces Epileptic Seizures by Increasing Glutamate Release - Emidio Beraldo Neto; Lucas Alves de Freitas; Daniel Carvalho Pimenta; Ivo Lebrun; Ana L. A. Nencioni (Toxins, 2020)
Here, we report the neurotoxic effects aroused by the intracerebral injection (in rats) of Tb1, which is a neurotoxin isolated from Tityus bahiensis scorpion venom. Biochemical analyses have demonstrated that this toxin is similar to the gamma toxin from T. serrulatus, which is a β-scorpion toxin that acts on sodium channels, causing the activation process to occur at more hyperpolarized membrane voltages. Male Wistar rats were stereotaxically implanted with intrahippocampal electrodes and cannulas for electroencephalographic recording and the evaluation of amino acid neurotransmitters levels. Treated animals displayed behavioral and electroencephalographic alterations similar to epileptiform activities, such as myoclonus, wet dog shakes, convulsion, strong discharges, neuronal loss, and increased intracerebral levels of glutamate. Scorpion toxins are important pharmacological tools that are widely employed in ion channel dysregulation studies. The current work contributes to the understanding of channelopathies, particularly epilepsy, which may originate, among other events, from dysfunctional sodium channels, which are the main target of the Tb1 toxin.